2022
DOI: 10.1016/j.ajog.2021.11.034
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth after the introduction of COVID-19 mitigation measures in Norway, Sweden, and Denmark: a registry-based difference-in-differences study

Abstract: Background Although some studies have reported a decrease in preterm birth following the start of the COVID-19 pandemic, the findings are inconsistent. Objective This study aimed to compare the incidences of preterm birth before and after the introduction of COVID-19 mitigation measures in Scandinavian countries using robust population-based registry data. Study Design This was a registry-based difference-in-differences study using births fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 49 publications
2
33
0
1
Order By: Relevance
“…A study that included population‐based data on live births and stillbirths in Norway, Sweden and Denmark has also been published. 16 This registry‐based study used the difference‐in‐differences method to analyse births from January 2014 to December 2020, before and after the introduction of COVID‐19 restrictions. The data were analysed for the 2 weeks before 12 March 2020, and the day after a global pandemic was declared, and 16 weeks after that date.…”
Section: Discussionmentioning
confidence: 99%
“…A study that included population‐based data on live births and stillbirths in Norway, Sweden and Denmark has also been published. 16 This registry‐based study used the difference‐in‐differences method to analyse births from January 2014 to December 2020, before and after the introduction of COVID‐19 restrictions. The data were analysed for the 2 weeks before 12 March 2020, and the day after a global pandemic was declared, and 16 weeks after that date.…”
Section: Discussionmentioning
confidence: 99%
“…So far, only one study has investigated potential long-term trends. That study summarized centrally reported data from Norway, Sweden and Denmark 22 . The results of that study and our work are congruent.…”
Section: Discussionmentioning
confidence: 99%
“…mobility patterns, and psychological responses to these, varied considerably between countries and over time 1 . The COVID-19 lockdown constitutes an important quasi-experiment with respect to identification of novel methods to prevent preterm birth (PTB) 3 .…”
Section: Tablementioning
confidence: 99%
“…Three subsequent studies, which included Danish data, all examined PTB rates without excluding multifetal pregnancies 3-5 . This makes data interpretation difficult, as multifetal pregnancies have a different set of risk factors for PTB, increased risk of adverse outcome, and a shorter expected pregnancy length.…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation